(untitled) (Eurasian Journal of Learning and Academic Teaching, 2022)
The article is dedicated to historical background of simultaneous interpreting. It is aimed at analyzing the main stages of simultaneous interpreting development. Highlighting historical events in simultaneous interpreting becomes a necessity nowadays when the cooperation between countries is developing rapidly. In view of this attention is drawn to the fact that interpreting has played a distinctive role in the relations between people who are living in different regions and have distinct origins since emergence of mankind